Моделювання процесу реєстрації електромагнітного випромінювання системами локації - Дацько, С. В.; Стрілкова, Т. О. (ХНУРЕ, 2025)
This work is dedicated to the development of a Monte Carlo simulation tool for electromagnetic radiation propagation and registration, focusing on stochastic medium and source parameters. The paper presents the simulation results, visualizing spatial-temporal characteristics of radiation upon detection. This method can be applied to optimize detection and tracking algorithms in localization systems, considering the statistical and spatial-energy properties of registered signals.
Keywords: система локації; реєстрація електромагнітного випромінювання